Sürekli ayaktan periton diyalizi hastalarında kardiyak troponin T'nin kardiyak olayları göstermede prognostik değeri - Duman, Dursun (My University, 2001)
Cardiovascular disease is the leading cause of morbidity and mortality in patients with end-stage renal disease. Cardiac troponins have recently been shown to predict cardiovascular events (CVE) in chronic hemodialysis patients. The aim of this study was to investigate the value of cardiac troponin T (cTnT) as a predictor of subsequent CVE in patients on continuous ambulatory peritoneal dialysis (CAPD). Sixty-five CAPD patients over 35 year old (29 females, mean age 56 ± 12 yrs) without any evidence of an acute coronary syndrome in the last 28 days were prospectively included and followed-up for 12 months. Ten (% 15) of these patients had previously documented coronary artery disease, which was either asymptomatic or clinically stable. Baseline cTnT was measured by the 3rd generation assay using electrochemiluminescence immunassay (ECLIA) method on the ELECSYS 2010 (Roche Diagnostics, Boehringer Mannheim, Germany). Study endpoints were defined as new myocardial infarction, unstable angina pectoris, coronary revascularization procedures including percutaneous coronary intervention or coronary artery by-pass graft surgery and sudden and nonsudden cardiovascular death. No correlation could be found between serum cTnT levels and serum urea, creatinine, CK, CK-MB levels, and the duration of dialysis. Twelve patients (18 %) had CVE, including 7 myocardial infarctions, 2 coronary revascularization procedures, 1 unstable angina, 1 sudden cardiac death, and 1 fatal peripheral vascular event. Twenty-three patients had cTnT levels a 0.05 ng/ ml and of these 12 had CVE. Thus the sensitivity of cTnT s. 0.05 ng/ ml in predicting CVE was 100 % and specificity was 79 %. The positive and negative predictive values were 52 % and 100 %, respectively (p < 0.0001). On the other hand 15 patients had cTnT levels â 0.1 44 ng/ ml; 9 of these suffering CVE. With this cut-off level, sensitivity was 75 %, however specificity improved to 89 %. The positive and negative predictive values were 60 % and 94 %, respectively (p < 0.0001). These results imply that a high baseline serum cTnT level (&0.05 ng/ ml) is highly sensitive and reasonably specific in predicting CVE within 12 months in CAPD patients either asymptomatic or stable of cardiovascular symptoms. cTnT levels equal or above 0.1 ng/ ml have a lower sensitivity but a remarkable specificity.
Keywords: Hastalıklar; Kalp damar sistemi hastalıkları; Kalp hastalıkları; Kardiyoloji; Teknoloji (Uygulamalı bilimler); Tıp; Tıp bilimleri